(untitled) - Jurasky, Daniel (Upper Saddle River, N.J., 2009)
This book introduction about words, speech, syntax, semantics and pragmatics, applications
Từ và ảnh,Xử lý ngôn ngữ tự nhiên nâng cao
Keywords: Computational linguistics,Automatic speech recognition,Ngôn ngữ máy tính,Nhận dạng nói tự động